2020
DOI: 10.1007/s00122-020-03715-9
|View full text |Cite
|
Sign up to set email alerts
|

QTL associated with gummy stem blight resistance in watermelon

Abstract: Key message We identified QTLs associated with gummy stem blight resistance in an interspecific F2:3Citrullus population and developed marker assays for selection of the loci in watermelon. Abstract Gummy stem blight (GSB), caused by three Stagonosporopsis spp., is a devastating fungal disease of watermelon (Citrullus lanatus) and other cucurbits that can lead to severe yield losses. Currently, no commercial cultivars with genetic resistance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 58 publications
2
41
0
Order By: Relevance
“…ClGSB5.1) identi ed by Gimode et al ( 2021), the marker most closely associated to Qgsb5.1 (ClGSB5.1-1) was included in the map (Fig. 2c) 17 . ClGSB5.1-1 mapped 44.5 cM outside the con dence interval of the current QTL and it was therefore concluded that the QTL identi ed in the current study represents a novel QTL (Qgsb5.2).…”
Section: Qtl-seqmentioning
confidence: 99%
See 1 more Smart Citation
“…ClGSB5.1) identi ed by Gimode et al ( 2021), the marker most closely associated to Qgsb5.1 (ClGSB5.1-1) was included in the map (Fig. 2c) 17 . ClGSB5.1-1 mapped 44.5 cM outside the con dence interval of the current QTL and it was therefore concluded that the QTL identi ed in the current study represents a novel QTL (Qgsb5.2).…”
Section: Qtl-seqmentioning
confidence: 99%
“…The species of Stagonosporopsis used by Lee et al (2021) is unknown. Gimode et al (2021) used a population derived from Crimson Sweet (C. lanatus) × PI 482276 (C. amarus) and S. citrulli isolate 12178A to map GSB resistance QTL on chromosomes 5 and 7 17 . Differences in the locations of these QTL, especially those derived from the same resistant parent (PI 189225), are likely due to either differences in resistance to the various species or isolates of Stagonosporopsis used for phenotyping or differences in phenotyping methodologies.…”
Section: Introductionmentioning
confidence: 99%
“… Moumni et al (2020) reported that the selection of healthy fruit is not sufficient to reduce the infection by this seedborne pathogen. On the other hand, cultural practices and fungicide application can have important roles in GSB management, although this pathogen has developed resistance to many fungicides that were previously very effective ( Finger et al, 2014 ; Gimode et al, 2020 ; Newark et al, 2020 ). Therefore, early diagnosis of this pathogen is a fundamental step in the management of these crop diseases ( Ora et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…No commercial cultivars with resistance to gummy stem blight are available, and so this disease has been frequently managed by fungicides application. As a result, several fungicides have lost their effectiveness against this disease following the development of resistance by S. cucurbitacearum [28,31]. Therefore, the development of alternative strategies to the use of synthetic fungicides for seed treatments is essential for both integrated pest management and organic agriculture.…”
Section: Introductionmentioning
confidence: 99%